Transferencia de tecnología en los PRODETER del estado de Morelos - Vázquez-Alvarado, Jorge Miguel Paulino; Hernández-Arenas, Marianguadalupe; Ramírez-Rojas, Sergio Gavino; Rangel-Estrada, Sandra Eloísa; Tavitas-Fuentes, Leticia; Trujillo-Campos, Alberto (Revista Mexicana de Ciencias Agrícolas, 2024)
The 2019 rural development program aimed to sustainably increase the productivity of family production units in rural areas in order to contribute to improving their income. The units served should be located in rural areas of priority attention and in localities of high and very high marginalization. To achieve the objective, territorial development projects were carried out, which would be aimed at strengthening production units and forming companies integrated into production chains. In this process, they would have technology and technical assistance. In the state of Morelos, eight territorial development projects were formed: agave, minor species, avocado, major species, fruit species, vegetables, corn-sorghum-amaranth, and nopal. The Zacatepec Experimental Field was in charge of technology transfer. In each project, it was carried out in three stages: in the first, a diagnosis of the production units was carried out, from which the problems and the technological model that would solve these problems emerged. Modules were established to transfer the technology, in which demonstrations were carried out, producers and extensionists were trained with courses and workshops, technological exchange trips were carried out and fold-outs and technological chart were printed. To address specific problems, visits to the plots or farms of some producers were scheduled. Although the resources arrived late, the programmed transfer was fulfilled, but it could not be continued because the duration of the program was short, so it could not be evaluated if productivity was improved.